2016
DOI: 10.1002/cpp.2006
|View full text |Cite
|
Sign up to set email alerts
|

First‐person Pronoun Use in Spoken Language as a Predictor of Future Depressive Symptoms: Preliminary Evidence from a Clinical Sample of Depressed Patients

Abstract: Naturally occurring individual differences in first-person singular pronoun use provide an unobtrusive way to assess patients' automatic self-focused attention. Frequent use of first-person singular pronouns predicts an unfavourable course of depression. Self-focused language might offer innovative ways of tracking and targeting therapeutic change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 50 publications
9
70
2
1
Order By: Relevance
“…Of note, earlier findings of a higher use of overall negative emotion words could not be replicated in the current study [34], [35]. A possible explanation is the diverse assessment of depression.…”
Section: Prediction Of Depressive Symptoms Through Word Usecontrasting
confidence: 94%
“…Of note, earlier findings of a higher use of overall negative emotion words could not be replicated in the current study [34], [35]. A possible explanation is the diverse assessment of depression.…”
Section: Prediction Of Depressive Symptoms Through Word Usecontrasting
confidence: 94%
“…Future studies are needed not only to confirm whether or not changes in self-evaluation influences outcome in different types of psychotherapy but also to better understand the related processes and helpful techniques that will eventually result in higher self-esteem. A recent empirical finding that may be of relevance here, is that heightened self-focused attention as evidenced in patients' language was associated with slower recovery from depression (Zimmermann, Brockmeyer, Hunn, Schauenburg, & Wolf, 2016). Based on the previous finding that cognitive errors of depressed patients are associated with the interpersonal patterns between patients and therapists, future studies should also include the therapeutic alliance as potential mediating variable.…”
Section: Prediction Of Outcome At Follow-upmentioning
confidence: 95%
“…Linguistic research has found a positive association between past-focused language and depressive symptoms (Habermas, Ott, Schubert, Schneider, & Pate, 2008;Rodriguez et al, 2010). Zimmermann, Brockmeyer, Hunn, Schauenburg, and Wolf (2017) found that first-person singular (FPS) pronoun use in semi-structured diagnostic interviews (e.g., "I was offended by his behaviour") was positively related to BDI score at both termination and follow-up. Van Staden (2006) noted that poor outcome cases evidenced significantly more negative words, such as never and not, in the initial sessions in comparison with cases that experienced positive change.…”
Section: Psychology Psychotherapy and The Study Of Languagementioning
confidence: 99%